Formation Of a Project Culture Among Future Teachers - Urazova Marina Batyrovna (Genius Journals, 2022)
The main purpose of the article is to discuss the factors that influence the formation of management culture in the context of improving modern education and their main features. In the process of developing the model, the author focuses on the formation of management competence in the forms of humanitarian education technology in the formation of three areas of training for management activities: targeted, educational, action and practical. Each of them suggests the formation of appropriate values for students of pedagogical universities. The author concludes that every child should have as high an education as possible, so the quality of education can only be improved if the education system is led by a strong, intelligent, knowledgeable and qualified, and most importantly, highly cultured leader
Keywords: Teacher-psychologist; model; motivation